Traditions of Jayawijaya Muslim Society: Some Perspectives from Islam and Customs - Ismail, Rudihartono; Asso , Hasan Abdul Rahman (Millah: Journal of Religious Studies, 2024)
This article explores the compromises made between local customs (adat) and Islamic religious practices in the daily lives of Muslim communities in Jayawijaya, Indonesia. Adat and Islam are two influential elements that profoundly shape societal norms, and their interaction often leads to a dynamic negotiation of values and practices. When Islamic teachings are introduced into a community with deeply rooted traditions, there is often tension between the demands of religion and established cultural customs. This phenomenon is not unique to Jayawijaya. Similarly, when Islam was first revealed in Arab society, it encountered established traditions and customs that had been passed on for generations. In Jayawijaya, local customs are deeply embedded in the lives of Muslims, including initiation ceremonies, marriages, funerals, and other sacred rituals. A significant aspect of these rituals is the communal pig feast, which traditionally occurs in the silimo (courtyard) of homes. Recognizing the need to harmonize these practices with Islamic teachings, the author endeavors to standardize these rituals by replacing pigs with animals that are halal (permissible) for consumption and aligning ceremonies with Islamic law. This study sheds light on the intricate balance between preserving cultural heritage and adhering to religious obligations, thereby providing a framework for similar contexts in which religion and tradition intersect.